An EFL student case study of English as a Foriegn language for writing present simple sentences-TEFL program portfolio - Sevy-Biloon, Julia Raina Fetima (2012)
This research report contains a student case study on writing present simple sentences and a TEFL program portfolio. The purpose of the case study was to show how a student learns to write simple sentences using grammar and other teaching techniques. The study shows the child’s progress over the six-week course and ends with the student’s thoughts about the course and the teacher’s recommendations for the students’ future in learning English. The student’s progress was recorded throughout the course and provides evidence of what the student learned in each class. The TEFL student portfolio shows the candidates progress in their master’s program over the last two years. The purpose was to demonstrate how assignments completed during the Master’s Program connect to the necessary teaching standards that are followed by students and teachers in the area of English as a second language. The research throughout the report implies the candidate has gained sufficient knowledge and skills through teaching courses, creating lesson plans and varying forms of assessment, and uses various techniques and methods to teach authentic fulfilling classes in English.